Technical Skill Analysis of Badminton Blow on Teenager Players of Pendowo Club Semarang (Journal of Physical Education and Sports, 2018)
Teenager players of Pendowo club still ignore the success and failure aspect in the blow technique skills done during the game. The purpose of this research is to find out how big the success and failure rate of badminton blow technique at teenager players of Pendowo club and to analyze the motion performance in badminton blow technique, which has the highest failure rate at teenager players of Pendowo club. This was descriptive research that, used survey method with observation sheet as the data collection technique. The population included were 16 teenager players of Pendowo club Semarang. Samples taken from the total sampling were 8 male and 8 female players. The results of this research are: the success rate of teenager players Pendowo club in short service is 97.74%, long service is 95.56%, lob is 94.10%, dropshot is 68.01%, and smash is 77.57%, while at the failure rate short service is 2.26%, long service is 4.44%, lob is 5.90%, dropshot is 31.99%, and smash is 22.43%, other result shows that the highest failure rate is the dropshot blow. The performance of this blow results that teenager players of Pendowo club in the preparation phase enters "Sufficient" category amounted 76.7%, the implementation phase includes "Sufficient" category amounted 73%, and the advanced phase enters "Sufficient" category resulted 70%.